C++ 2013 for C# Developers - Wills, Dean C. (Apress : Imprint: Apress, 2014)
C++ 2013 for C# Developers provides a fast-track to C++ proficiency forthose already using the C# language at an advanced level. Beginning with a detailed explanation of the mechanics of C++'s execution sequence, its grammar, syntax and data access you'll quickly learn the similarities and differences between C++ and C#. The second and third partsof the of the book are devoted to a detailed deep-dive into C++ development to provide clear information and advice about how to use the languageeffectively.